Changes in screening colonoscopy following Medicare reimbursement and cost‐sharing changes - Song, Lina D.; Newhouse, Joseph P.; Garcia‐De‐Albeniz, Xabier; Hsu, John (Health services research, 2019)
Objectives To compare existing algorithms for classifying screening vs diagnostic colonoscopies and to quantify the increase in screening colonoscopy rates when Medicare began reimbursement in 2001 and when the Affordable Care Act (ACA) eliminated cost‐sharing. Data Sources Twenty percent random sample of fee‐for‐service (FFS) Medicare claims, 2000‐2012. Study Design Using recent administrative codes as tarnished gold standards, we examined the sensitivity and specificity of five published algorithms for classifying colonoscopies and calculated annual screening colonoscopy rates. We estimated the change in rates after Medicare began reimbursement and used difference‐in‐differences analysis to estimate the effects of eliminating cost‐sharing by comparing states with and without a mandate to cover screening colonoscopy prior to the ACA. Findings Model‐based algorithms have higher sensitivity (0.53‐0.99) than expert‐based algorithms (0.35‐0.39), but lower specificity (0.43‐0.65 vs 0.79‐0.88). All algorithms detected increases in screening from both Medicare's reimbursement change (range: 24‐93/10 000) and the 2011 cost‐sharing change (range: 1.1‐34/10 000). Difference‐in‐difference estimates of the ACA's effect varied from 51 to 155 tests per 10 000 depending on the algorithm. Conclusions Screening colonoscopy rates increased after eliminating cost‐sharing in 2011, but the increase's size varied depending on the algorithm used to classify the indication. Improvements are needed in Medicare coding for screening.